Immediate natural tooth bridge - Greer, Anna; Husain, Juzaily; Martin, Nicolas (George Warman Publications (UK) Ltd., 2018)
This article describes four cases in which immediate natural tooth bridges have been provided. Four different techniques are described for creating these. The four different retainer types discussed are silanated glass fibres impregnated with PMMA and bis-GMA, laboratory-made metal wings, metal mesh and mesh-type titanium wire. With the support of photographs and diagrams, the techniques for each retainer type are described. The final section of this article discusses the factors that affect the prognosis of immediate natural tooth bridges. Providing information on prognosis is an important part of the consent process; this includes patient factors and clinician factors.